Duality, Matroids, Qubits, Twistors, and Surreal Numbers - Nieto, J. A. (Frontiers in Physics, 2018)
We comment on the possibility that the various concepts such as duality, matroids, qubits, twistors and surreal numbers must be considered as underlying mathematical structures in quantum gravity. Moreover, we argue that via the Grassmann-Plücker relations, these apparent unrelated concepts are, in fact, deeply connected .